Synthesis and Application of Amino-Carboxylic Based High Performance Superplasticizer for Concrete - Xu, Chen (Asian Journal of Chemistry, 2014)
Aminosulfonic-based superplasticizers have been considered as a high performance superplasticizers in virtue of their superior properties. However, disadvantages such as high cost and complicated synthesis process result in limited application for these superplasticizers. In this paper, we present a novel synthesis route for amino-carboxylic-based high performance superplasticizer. In this process, carboxylic group was added to the molecules of traditional aminosulfonic-based superplasticizer by using distinctive process, feedstock and ratio. This sample has shown various advantages including low cost, high performance and the potential for large-scale application in the future.